Aktywnosc wybranych enzymów lizosomalnych w surowicy krwi kajakarzy po kriostymulacji ogólnoustrojowej - Wozniak, A.; Mila-Kierzenkowska, C.; Drewa, T.; Drewa, G.; Wozniak, B.; Olszewska, D.; Malinowski, D.; Rakowski, A.; Brzuchalski, M. (Medycyna sportowa, 2001)
Background. Activity of three lysosomal hydrolases: arylsulphatase(E.C. 3.1.6.1.), acid phosphatase (E.C. 3.1. 3.2) and cathepsin D (E.C. 3.4.4.23.) was assayed in blood serum of intense training sportsmen. Material and methods. The study was performed on 9 kayakers of Olympic Team, which were put to a whole body cryostimulation. Venous blood samples were taken: before the start of research (control), after 5-th and 10-th day of intense training joint with a whole body cooling in cryogenic chamber and when cryostimulation had already been finished in 17-th, 24-th and 31-st day of further intense training. Results. Statistically significant decrease of arylsulphatase activity in comparison to control was noticed after 5-th and in 31-th day of training. Activity of arylsulphatase decreased from 4,48 respectively to 3,07 x 10-3 nM 4-NC/ mg of protein/ min after 5-th day of cryostimulation and training and to 2.76 x 10-3 nM 4-NC/ mg of protein/ min after 31-st day of training. However no statistically significant differences in activities of acid phosphatase and cathepsin D were observed during the time of experiment.